Effective temperature of ionizing stars in extragalactic H II regions : II. Nebular parameter relationships based on CALIFA data - Zinchenko, Igor A. (2018)
We calculate the effective temperature (Teff) of ionizing star(s), the oxygen abundance of the gas phase (O/H)⁠, and the ionization parameter U for a sample of H II regions located in the discs of 59 spiral galaxies in the redshift range 0.005 < z < 0.03. We use spectroscopic data taken from the CALIFA data release 3 (DR3) and theoretical (for Teff and U) and empirical (for O/H) calibrations based on strong emission lines. We consider the spatial distribution and radial gradients of these parameters in each galactic disc for the objects in our sample. Most of the galaxies in our sample (∼70 per cent) show positive Teff radial gradients, although some exhibit negative or flat ones. The median value of the Teff radial gradient is 0.762 kK/R25. We find that the radial gradients of both log U and Teff depend on the oxygen abundance gradient, in the sense that the gradient of log U increases as the log(O/H) gradient increases while there is an anti-correlation between the gradient of Teff and the oxygen abundance gradient. Moreover, galaxies with flat oxygen abundance gradients tend to have flat log U and Teff gradients as well. Although our results are in agreement with the idea of the existence of positive Teff gradients along the disc of the majority of spiral galaxies, it seems that this is not a universal property for these objects.